ASSESSMENT OF YIELD LOSSES DUE TO LEAF BLOTCH OF TURMERIC CAUSED BY TAPHRINA MACULANS BUTLER - GOPALKUMAR CHOPADA; K. B. RAKHOLIYA (The Bioscan, 2015)
Field experiment was carried out at two different locations of South Gujarat viz; Tarkani village of Surat district and at Navsari district during 2014-15 to study yield loss caused by leaf blotch disease in turmeric crop. Result reveals that the avoidable yield loss due to leaf blotch (Taphrina maculans Butler) was estimated to be 36.95% at Navsari and 36.36% at Tarkani village of Surat district and 71.70% and 72.97% disease was controlled by protecting the turmeric plots at Navsari and Tarkani respectively by two foliar sprays of propiconazole (0.025%). Leaf blotch may cause loss up to 36 % in turmeric crop and around 72 % control of disease may achieve by giving two foliar sprays of propiconazole (0.025%) first spray at initiation of disease and second spray after fifteen days of first spray.